PEMBINAAN TENTANG RURAL SUSTAINABILITY: SEBUAH LAPORAN KEGIATAN STUBE-HEMAT MAHASISWA SEKOLAH TINGGI TEOLOGI ARASTAMAR BENGKULU - Made Nopen Supriadi; Yohanes Dian Alpasa; Iman Kristina Halawa; Vincesius (Jurnal PKM Setiadharma, 2022)
Rural Sustainability is an important topic today. Rural sustainability is threatened with stagnation because many students from rural areas study in cities with less focus on rebuilding villages. Rural sustainability that receives village funds also faces problems because there are still unscrupulous village officials who corrupt village funds. Through the Implementation of Community Service held by Stube-HEMAT and STTAB students with the seminar method from the Multiplicator and Stube-HEMAT facilitator. The PkM activity resulted in breakthrough thoughts and important insights for theology students to play a role in the sustainability of village development, in various ways, both contributing to ideas and practically becoming village leaders with morals and integrity.